Criminal Procedure Procedure Anomalies in Modern Legal Dynamics: The Urgency of Legislative Reform to Ensure Legal Certainty - Muhamad Zaenal Arifin (Rechtsvinding, 2026)
The implementation of the Criminal Procedure Code (KUHAP) in Indonesia still faces various structural and normative challenges, which are reflected in the procedural anomalies that occur in the field. These anomalies, such as unclear detention and investigation procedures, have created legal uncertainty that harms human rights and lowers the credibility of the criminal justice system. This study aims to identify gaps in the Criminal Code and assess the urgency of legislative reform needed to address these problems. The approach used in this study is a qualitative literature study, by analyzing various literature sources that include books, scientific articles, and relevant research reports. The findings of the study show that uncertainty in the duration of detention, weaknesses in the protection of suspects' rights, and the unpreparedness of the Indonesian legal system to accommodate modern technology are the main factors that worsen the effectiveness of the justice system. Therefore, comprehensive reform of the Criminal Procedure Code, including harmonization with international standards, technological integration through legal digitalization (e-Justice), and strengthening the independence of judicial institutions, is an urgent need to improve legal certainty, transparency, and human rights protection. The recommendations put forward in this study include expanding oversight of law enforcement officials, drafting regulations that accommodate electronic evidence, and public involvement in formulating legal policies to create a fairer and more efficient justice system.